The computer as an educational tool [electronic resource] : productivity and problem solving - 494401 Forcier, Richard C.; Descy, Don E. (Upper Saddle River, NJ : Pearson/Merrill/Prentice Hall, 2008)
Includes bibliographical references and indexes